Uso de las TIC como apoyo al proceso de aprendizaje autónomo (Papeles, 2009)
This reflective article deals with the possibility of having TIC as tools for developing communicative competences and to promote autonomous learning. This project elaborates on the autonomy concept and its relationships with knowledge and moral. On the other hand, it focuses on discussing TIC as educative processes while it clarifies that it is necessary to learn how to interpret their own language; in this way, will be possible to start formative processes.
Keywords: Communicative competences, information, educative processes, autonomy, learning tools.